1992
DOI: 10.1007/bf02381201
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake, digestion and passage of the proboscis monkey (Nasalis larvatus) in captivity

Abstract: ABSTRACT. Feeding trials were conducted with a troop of six proboscis monkeys (Nasalis larvatus) at the New York Zoological Park to quantify aspects of digestive physiology. Diets consumed comprised, on an as-fed basis, 55~ browse and green produce, 1107o fruit, 9070 commercial primate diets, 9070 root vegetables, and 1607o miscellaneous items. Total feed intake averaged 1207o of body mass; dry matter intake was 307o. Dry matter and plant cell wall disappearance exceeded 80070. Passage marker studies (three 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
6

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 11 publications
(8 reference statements)
2
37
6
Order By: Relevance
“…Our results suggest that proboscis monkeys, which have a multichambered stomach similar to ruminants [Chivers, 1994], may devote a large proportion of their activity budget to resting to aid in the digestion of foods with high levels of cellulose as reported in other colobine species (e.g., Trachypithecus francoisi, 52 % of time spent resting) [Zhou et al, 2007]; Presbytis thomasi, 59% [Stanford, 1991a]; Colobus vellerosus, 59% [Teichroeb et al, 2003]; and C. guereza, 63% [Fashing, 2001a]. Feeding trials of captive proboscis monkeys support this suggestion because transit time (elapsed time from feeding to appearance of a marker in feces) is 14 hr and retention time (time between appearance of 5 and 80% of the markers) is 52 hr [Dierenfeld et al, 1992]. Further, as Fashing 2007 provides data supporting a positive relationship between time resting and body size among African colobines, proboscis monkeys, which are the largest colobines, appear to fit this pattern.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our results suggest that proboscis monkeys, which have a multichambered stomach similar to ruminants [Chivers, 1994], may devote a large proportion of their activity budget to resting to aid in the digestion of foods with high levels of cellulose as reported in other colobine species (e.g., Trachypithecus francoisi, 52 % of time spent resting) [Zhou et al, 2007]; Presbytis thomasi, 59% [Stanford, 1991a]; Colobus vellerosus, 59% [Teichroeb et al, 2003]; and C. guereza, 63% [Fashing, 2001a]. Feeding trials of captive proboscis monkeys support this suggestion because transit time (elapsed time from feeding to appearance of a marker in feces) is 14 hr and retention time (time between appearance of 5 and 80% of the markers) is 52 hr [Dierenfeld et al, 1992]. Further, as Fashing 2007 provides data supporting a positive relationship between time resting and body size among African colobines, proboscis monkeys, which are the largest colobines, appear to fit this pattern.…”
Section: Discussionmentioning
confidence: 74%
“…Yeager [1989] suggested that proboscis monkeys appear to enrich their diet with seeds. Although proboscis monkeys are probably efficient digesters of plant cell wall constituents [Dierenfeld et al, 1992], they may prefer unripe fruits and seeds, over leaves because they are composed of more easily digested carbohydrates than young leaves [Davies et al, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…Our data point to an apparent digestibility of lignin of about 35%. Although it is generally accepted that lignin can neither be digested nor fermented, some authors have demonstrated that lignin apparently can be digested by leaf-eating monkeys (2,7,10). However, the observed digestibility of lignin has been ascribed to methodological error (9), as described by Watkins et al (10).Despite this, it cannot be excluded that leaf-eating monkeys have intestinal bacteria capable of breaking down lignin.…”
Section: Discussionmentioning
confidence: 99%
“…They are closer to those found in more omnivorous species which are known to feed on over 40% leaves, such as Alouatta palliata and A. seniculus (MRT of 18-30 h; TT of 20.4 h) [5,6] or Nasalis larvatus (MRT of 49 h; TT of 14 h) [7], One cannot exclude the possibility that captivity modifies GPR, which is positively related to the proportion of dietary fibre in primates and other mammals [10,12,13]. However, it has been shown that captive mon keys fed on diets very similar to those of this study [5] had very different transit times de pending on the species.…”
Section: Discussionmentioning
confidence: 99%